Attenuation of diet-induced hypothalamic inflammation following bariatric surgery in female mice - Mary K. Herrick; Kristin M. Favela; Richard B. Simerly; Naji N. Abumrad; Nathan C. Bingham (BMC, 2018)
Abstract Background Exposure of rodents to chronic high-fat diet (HFD) results in upregulation of inflammatory markers and proliferation of microglia within the mediobasal hypothalamus. Such hypothalamic inflammation is associated with metabolic dysfunction, central leptin resistance, and maintenance of obesity. Bariatric surgeries result in long-term stable weight loss and improved metabolic function. However, the effects of such surgical procedures on HFD-induced hypothalamic inflammation are unknown. We sought to characterize the effects of two bariatric surgical procedures, Roux-en-Y gastric bypass (RYGB) and biliary diversion (BD-IL), in female mice with particular emphasis on HFD-induced hypothalamic inflammation and microgliosis. Methods RYGB and BD-IL were performed on diet-induced obese (DIO) mice. Quantitative RT-PCR and fluorescent microscopy were used to evaluate hypothalamic inflammatory gene expression and microgliosis. Results were compared to lean (CD), DIO sham-surgerized mice (DIO-SHAM), and dietary weight loss (DIO-Rev) controls. Results In female mice, RYGB and BD-IL result in normalization of hypothalamic inflammatory gene expression and microgliosis within 8 weeks of surgery, despite ongoing exposure to HFD. Paralleling these results, the hypothalamic expression levels of the orexigenic neuropeptide Agrp and the anorexic response of surgical mice to exogenous leptin were comparable to lean controls (CD). In contrast, results from DIO-Rev mice were comparable to DIO-SHAM mice, despite transition back to standard rodent show and normalization of weight. Conclusion Bariatric surgery attenuates HFD-induced hypothalamic inflammation and microgliosis and restores leptin sensitivity, despite ongoing exposure to HFD.